Assessing the Macroeconomic Effects of Water Scarcity in South Africa using a CGE Model - (:unkn) unknown (My University, 2023)
We develop a dynamic computable general equilibrium (CGE) model to assess the macroeconomic impacts of water scarcity and water (in)security in South Africa. The CGE model which includes a detailed representation of water resources (surface water, groundwater, wastewater, and seawater) has been calibrated with an updated social accounting matrix enabling to conduct policy simulations up to 2030. With the 17% expected increase of water scarcity (population growth, climate change, and poor management of water resources), the CGE model predicts a decrease of South African GDP by −0.44% in 2030. The long-term impact of water scarcity varies from one sector to another, the most negatively impacted sectors being those related to water. Due to water scarcity, unemployment will increase in the short term by 0.76%. In the long term (2030), unemployment is however expected to recover its baseline level. The increase in water scarcity is also predicted to have a negative impact on household welfare, household consumption being reduced by −0.47% in 2030. A particular concern for policy-makers might be that low-income households are expected to be more impacted by water scarcity than high-income households. Some policies may mitigate the negative impacts of water scarcity, the most promising ones being to promote water saving and to decrease non-revenue water.
Keywords: African Research